Deletion of AMP-activated protein kinase impairs metastasis and is rescued by ROS scavenging or ectopic CD36 expression - Gopalakrishnan Ramakrishnan; Alexander R. Terry; Veronique Nogueira; Ahmed Magdy; Nissim Hay (Cell Reports)
Summary: AMPK’s role in tumor initiation and progression is controversial. Here, we provide genetic evidence that AMPK is required for metastasis in mouse models of breast cancer. In a mouse model of spontaneous breast cancer metastasis, the deletion of AMPK before and after tumor onset decreased breast cancer metastasis, and similar results were obtained after AMPK deletion in breast cancer cell lines. The deletion of AMPK induces reactive oxygen species (ROS) levels in vitro and lipid oxidation in vivo, which likely impede metastasis. Indeed, antioxidants restore the ability of AMPK-deficient tumors to metastasize. By inhibiting acetyl-coenzyme A (CoA) carboxylases 1 and 2, AMPK maintains NADPH levels by reducing NADPH consumption in fatty acid synthesis and increasing NADPH generation via fatty acid oxidation, thus increasing the dependency on auxotrophic fatty acids. Consistently, AMPK is required for the expression of the fatty acid transporter CD36 in tumors, and ectopic expression of CD36 in AMPK-deficient cells restored their ability to metastasize.